The cymothoid isopod Anilocra chromis is negatively associated with multiple metrics of host condition in the Caribbean damselfish Chromis multilineata - Jan-Alexis Barry; Kyle G. Jerris; Teresa R. Turner; Jenilee B. Robinson; Matthew D. Nicholson; Paul C. Sikkel (Marine Biology, 2026)
Parasitism is widespread among fishes in nature and can have significant impacts on individuals, populations, and communities. The family Cymothoidae includes over 380 species of parasitic isopods that infect a wide variety of host fishes, mostly in tropical and subtropical oceans. Despite their conspicuous nature, spatiotemporal patterns of infestation and effects on hosts have been studied for only a small percentage of species. The brown chromis ( Chromis multilineata ) is a common planktivorous damselfish associated with reefs in the tropical western Atlantic. Brown chromis are frequently infested with the large cymothoid isopod Anilocra chromis. In this study, we quantified the prevalence of infection among five sites and over two years in the US Virgin Islands (before and after major hurricanes). We further quantified the relationship between Anilocra infection status and the coinfection of other parasites as well as three metrics of potential impact: gonadal development, rate of food intake, and locomotion. Our results show that parasite prevalence differed significantly among sites. Additionally, while there was variation in coinfection with other parasites among sites, there was no relationship between the presence of Anilocra and the abundance of other parasites. There was a significant negative effect of Anilocra infection on male chromis gonads, feeding behavior (as determined by a decrease in bite-rates), and locomotion (as determined by an increase in fin-beats). Overall, these findings suggest that parasitism by Anilocra chromis is negatively associated with multiple metrics of fitness and health in host fishes, and thus likely has consequences at the population level.

Artificial Intelligence-Assisted Systematic Literature Reviews in Metabolic Phenotyping: A Methodological Framework and Validation Study - Maartje Cox; Javier Osorio Mosquera; Shaimaa Khandaker; Samuele Sala; Julien Wist; Jeremy K. Nicholson; Elaine Holmes; Timothy Fairchild; Nathan G. Lawler (Phenomics, 2026)
Systematic literature reviews are widely acknowledged to be at the top of most evidence hierarchies but are very time-consuming and labour-intensive. The advent of artificial intelligence (AI) offers possibilities to accelerate the review process. We propose a systematic literature review protocol that incorporates AI and evaluate the accuracy of AI against a human-constructed gold standard. Human researchers performed a systematic literature review on the PubMed metabolomic literature investigating Long COVID. OpenAI model o3-mini was then used via the application programming interface to carry out the three key stages of a systematic literature review: 1) screening articles for inclusion criteria, 2) evaluating articles' risk of bias (RoB) using a customised metabolomics tool based on well-established quality criteria, and 3) extracting data from articles. The performance of AI was evaluated against a manually created reference by the assessment of accuracy, negative predictive value, precision, sensitivity, specificity, F1 score, and Cohen's kappa. Out of the 320 identified articles, 33 met all inclusion criteria. AI performed screening, RoB assessment, and data extraction with mean accuracies of 92.7% ± 4.9%, 91.9% ± 5.9%, and 92.0% ± 9.2%, respectively, in ~ 10 h and at a cost of ~ 15.35 USD, while human reviewers took ~ 116 h, equivalent to ~ 2000 USD at minimum wages, to complete these steps in duplicate. OpenAI model o3-mini can independently complete the three main stages of systematic literature reviews in the metabolomics domain, thus considerably reducing the time to complete such reviews, at minimal cost. Nonetheless, human reviewers should always verify the AI-generated output to ensure robustness.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Further reverberations of the 1983 impact with Saturn’s C ring - Richard G. French; Philip D. Nicholson; Matthew M. Hedman; Heikki Salo; Essam A. Marouf; Colleen A. McGhee-French; Nicole Rappaport; Joshua Colwell; Richard Jerousek; Victor M. Afigbo; Sophia Flury; Jolene Fong; et al. (Icarus, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Helium, carbon and nitrogen isotope evidence for slab influence on volcanic gas emissions at Rabaul caldera, Papua New Guinea - B.T. McCormick Kilbride; P.H. Barry; T.P. Fischer; G. Holland; M. Hudak; S. Nowicki; C. Ballentine; M.D. Fox; M. Höhn; I. Itikarai; M.D. Johnson; K. Mulina; et al. (Chemical Geology, 2024)

C9orf72-Associated Dipeptide Repeat Expansions Perturb ER-Golgi Vesicular Trafficking, Inducing Golgi Fragmentation and ER Stress, in ALS/FTD - Jessica Sultana; Audrey M. G. Ragagnin; Sonam Parakh; Sayanthooran Saravanabavan; Kai Ying Soo; Marta Vidal; Cyril Jones Jagaraj; Kunjie Ding; Sharlynn Wu; Sina Shadfar; Emily K. Don; Anand Deva; et al. (Molecular Neurobiology, 2024)
Hexanucleotide repeat expansions (HREs) in the chromosome 9 open reading frame 72 ( C9orf72 ) gene are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both are debilitating neurodegenerative conditions affecting either motor neurons (ALS) in the brain and spinal cord or neurons in the frontal and/or temporal cortical lobes (FTD). HREs undergo repeat-associated non-ATG (RAN) translation on both sense and anti-sense strands, generating five distinct dipeptide repeat proteins (DPRs), poly-GA, -GR, -GP, -PA and -PR. Perturbed proteostasis is well-recognised in ALS pathogenesis, including processes affecting the endoplasmic reticulum (ER) and Golgi compartments. However, these mechanisms have not been well characterised for C9orf72-mediated ALS/FTD. In this study we demonstrate that C9orf72 DPRs polyGA, polyGR and polyGP (× 40 repeats) disrupt secretory protein transport from the ER to the Golgi apparatus in neuronal cells. Consistent with this finding, these DPRs also induce fragmentation of the Golgi apparatus, activate ER stress, and inhibit the formation of the omegasome, the precursor of the autophagosome that originates from ER membranes. We also demonstrate Golgi fragmentation in cells undergoing RAN translation that express polyGP. Furthermore, dysregulated ER-Golgi transport was confirmed in C9orf72 patient dermal fibroblasts. Evidence of aberrant ER-derived vesicles in spinal cord motor neurons from C9orf72 ALS patients compared to controls was also obtained. These data thus confirm that ER proteostasis and ER-Golgi transport is perturbed in C9orf72-ALS in the absence of protein over-expression. Hence this study identifies novel molecular mechanisms associated with the ER and Golgi compartments induced by the C9orf72 HRE.

Pollination deficits and their relation with insect pollinator visitation are cultivar-dependent in an entomophilous crop - Maxime Eeraerts; Stan Chabert; Lisa W. DeVetter; Péter Batáry; John J. Ternest; Kris Verheyen; Kyle Bobiwash; Kayla Brouwer; Daniel García; G. Arjen de Groot; Jason Gibbs; Lauren Goldstein; et al. (Agriculture, Ecosystems & Environment, 2024)

The Uranus system from occultation observations (1977–2006): Rings, pole direction, gravity field, and masses of Cressida, Cordelia, and Ophelia - Richard G. French; Matthew M. Hedman; Philip D. Nicholson; Pierre-Yves Longaretti; Colleen A. McGhee-French (Icarus, 2024)

The complex shape of the outer edge of Saturn’s B ring, as observed in Cassini occultation data - Richard G. French; Philip D. Nicholson; Colleen A. McGhee-French; Pierre-Yves Longaretti; Matthew M. Hedman; Joshua Colwell; Essam A. Marouf; Nicole Rappaport; Sophia Flury; Jolene Fong; Ryan Maguire; Glen Steranka (Icarus, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Effect of light spectra on cereal fungal pathogens, a review - M. Cerón-Bustamante; E. Balducci; G. Beccari; P. Nicholson; L. Covarelli; P. Benincasa (Fungal Biology Reviews, 2023)

Mapping connectivity and conservation opportunity on agricultural lands across the conterminous United States - Justin P. Suraci; Caitlin E. Littlefield; Charlie C. Nicholson; Mitchell C. Hunter; Ann Sorensen; Brett G. Dickson (Biological Conservation, 2023)

The seven-lobed shape of the outer edge of Saturn’s A ring - Philip D. Nicholson; Richard G. French; Colleen A. McGhee-French; Pierre-Yves Longaretti; Matthew M. Hedman; Maryame El Moutamid; Joshua Colwell; Essam A. Marouf; Nicole Rappaport; Sophia Flury; Jolene Fong; Ryan Maguire; et al. (Icarus, 2023)

Designing and managing biodiverse streetscapes: key lessons from the City of Melbourne - Hui-Anne Tan; Lee Harrison; Jeff Nelson; Maggie Lokic; John P. Rayner; Caragh G. Threlfall; Jessica Baumann; Adrian Marshall; Mark Callow; Jessica Peeler; Rebecca Korossy-Horwood; Chris Nicholson; et al. (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Finding Oxford’s medieval Jewry using organic residue analysis, faunal records and historical documents - J. Dunne; E. Biddulph; P. Manix; T. Gillard; H. Whelton; S. Teague; C. Champness; L. G. Broderick; R. Nicholson; P. Blinkhorn; E. Craig-Atkins; B. Jervis; et al. (Archaeological and Anthropological Sciences, 2021)
Food is often one of the most distinctive expressions of social, religious, cultural or ethnic groups. However, the archaeological identification of specific religious dietary practices, including the Jewish tradition of keeping kosher , associated with ritual food practices and taboos, is very rare. This is arguably one of the oldest known diets across the world and, for an observant Jew, maintaining dietary laws (known as Kashruth) is a fundamental part of everyday life. Recent excavations in the early medieval Oxford Jewish quarter yielded a remarkable assemblage of animal bones, marked by a complete absence of pig specimens and a dominance of kosher (permitted) birds, domestic fowl and goose. To our knowledge, this is the first identification of a Jewish dietary signature in British zooarchaeology, which contrasted markedly with the previous Saxon phase where pig bones were present in quantity and bird bones were barely seen. Lipid residue analysis of pottery from St Aldates showed that vessels from the possible Jewish houses were solely used to process ruminant carcass products, with an avoidance of pig product processing, correlating well with the faunal data. In contrast, lipid analysis of pottery from comparative assemblages from the previous Saxon phase at the site and a contemporaneous site in the city, The Queen’s College, shows that the majority of these vessels appear to have been used to process mixtures of both ruminant and non-ruminant (pig) products. Here, the combination of organic residue analysis, site excavation and animal and fish bone evidence was consistent with the presence of Jewish houses in eleventh- and twelfth-century St Aldates, Oxford, hitherto only suspected through documentary information. This is the first identification of specific religious dietary practices using lipid residue analysis, verifying that, at least 800 years ago, medieval Jewish Oxford communities practised dietary laws known as Kashruth.

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats - Yilin Mao; Tara Nguyen; Ryan S. Tonkin; Justin G. Lees; Caitlyn Warren; Simon J. O’Carroll; Louise F. B. Nicholson; Colin R. Green; Gila Moalem-Taylor; Catherine A. Gorrie (Experimental Brain Research, 2017)

Potentiation of the NO-cGMP pathway and blood flow responses during dynamic exercise in healthy humans - Jacqueline K. Limberg; Katherine R. Malterer; J. Mikhail Kellawan; William G. Schrage; Brad W. Wilkins; Wayne T. Nicholson; John H. Eisenach; Michael J. Joyner; Timothy B. Curry (European Journal of Applied Physiology, 2017)

Like mother like nest: similarity in microbial communities of adult female Pied Flycatchers and their nests - Anne E. Goodenough; Bethan Stallwood; Shantelle Dandy; Thomas E. Nicholson; Hannah Stubbs; David G. Coker (Journal of Ornithology, 2017)

The impact of repetition mechanics on the adaptations resulting from strength-, hypertrophy- and cluster-type resistance training - G. Nicholson; T. Ispoglou; A. Bissas (European Journal of Applied Physiology, 2016)

Development of a Control Strategy for Benzene Impurity in HPMCAS-Stabilized Spray-Dried Dispersion Drug Products Using a Science-Based and Risk-Based Approach - Hongfei Yue; Sarah J. Nicholson; Joel D. Young; Daniel Hsieh; Rodney J. Ketner; Robert G. Hall; Jeremy Sackett; Elizabeth C. Banks; John A. Castoro; Michael E. Randazzo (Pharmaceutical Research, 2015)

A detailed rainfall climatology for Malawi, Southern Africa - S. E. Nicholson; D. Klotter; G. Chavula (International Journal of Climatology, 2014)
This article presents a detailed analysis of the mean rainfall climatology of Malawi and an overview of interannual variability. Monthly and seasonal means, the seasonal cycle and intraseasonal variability are examined. This includes an analysis of the onset, end and duration of the rainy season. The study reveals two surprising features of the rainfall regime. One is a region with a strong rainfall maximum in the austral autumn along the western shore of Lake Malawi. The second is a brief period of reduced rainfall in mid‐February that appears to signal a shift in the prevailing rainfall and circulation regime. The prevailing atmospheric circulation is markedly different before and after the break, as are the characteristics of the rainy season. Overall, the results indicate that the early (pre‐break) rainy season (December–February) is dominated by tropical influences, the late (post‐break) rainy season (March–April) is dominated by extra‐tropical influences and interannual variability in these two periods is uncorrelated. The results also demonstrate two aspects of interannual variability: the dominant contribution of the MA season and the frequent opposition between northern and southern Malawi.

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Comprehensive Ubiquitin E2 Profiling of Ten Ubiquitin E3 Ligases - Jeffrey G. Marblestone; Samir Butt; Devin M. McKelvey; David E. Sterner; Michael R. Mattern; Benjamin Nicholson; Michael J. Eddins (Cell Biochemistry and Biophysics, 2013)

Limitations and potentials of dual-purpose cow herds in Central Coastal Veracruz, Mexico - Victor Antonio Absalón-Medina; Robert W. Blake; Danny Gene Fox; Francisco I. Juárez-Lagunes; Charles F. Nicholson; Eduardo G. Canudas-Lara; Bertha L. Rueda-Maldonado (Tropical Animal Health and Production, 2012)

Economic analysis of alternative nutritional management of dual-purpose cow herds in central coastal Veracruz, Mexico - Victor Antonio Absalón-Medina; Charles F. Nicholson; Robert W. Blake; Danny Gene Fox; Francisco I. Juárez-Lagunes; Eduardo G. Canudas-Lara; Bertha L. Rueda-Maldonado (Tropical Animal Health and Production, 2012)

Quantification of the relationship between the environment and Fusarium head blight, Fusarium pathogen density, and mycotoxins in winter wheat in Europe - Alissa B. Kriss; Pierce A. Paul; Xiangming Xu; Paul Nicholson; Fiona M. Doohan; Laszlo Hornok; Alberto Rietini; Simon G. Edwards; Laurence V. Madden (European Journal of Plant Pathology, 2012)

Modelling experimental uveitis: barrier effects in autoimmune disease - David Nicholson; Emma C. Kerr; Owen G. Jepps; Lindsay B. Nicholson (Inflammation Research, 2012)

The Multifaceted Roles of USP7: New Therapeutic Opportunities - Benjamin Nicholson; K. G. Suresh Kumar (Cell Biochemistry and Biophysics, 2011)

Targeting the Ubiquitin E3 Ligase MuRF1 to Inhibit Muscle Atrophy - Michael J. Eddins; Jeffrey G. Marblestone; K. G. Suresh Kumar; Craig A. Leach; David E. Sterner; Michael R. Mattern; Benjamin Nicholson (Cell Biochemistry and Biophysics, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

An evaluation of airborne laser scan data for coalmine subsidence mapping - D. R. Palamara; M. Nicholson; P. Flentje; E. Baafi; G. M. Brassington (International Journal of Remote Sensing, 2007)

Caspase-3 cleaves the formin-homology-domain-containing protein FHOD1 during apoptosis to generate a C-terminal fragment that is targeted to the nucleolus - Isabelle Ménard; François G. Gervais; Donald W. Nicholson; Sophie Roy (Apoptosis, 2006)

Liquefaction evaluation discrepancies in tropical lagoonal soils - Peter G. Nicholson (Geotechnical and Geological Engineering, 2006)

A Method for Extracting RNA from Dormant and Germinating Bacillus subtilis Strain 168 Endospores - R. Moeller; G. Horneck; P. Rettberg; H.-J. Mollenkopf; E. Stackebrandt; W. L. Nicholson (Current Microbiology, 2006)

Basidiochrome – A Novel Siderophore of the Orchidaceous Mycorrhizal Fungi Ceratobasidium and Rhizoctonia spp. - K. Haselwandter; V. Passler; S. Reiter; D. G. Schmid; G. Nicholson; P. Hentschel; K. Albert; G. Winkelmann (BioMetals, 2006)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Environmental Metabonomics: Applying Combination Biomarker Analysis in Earthworms at a Metal Contaminated Site - Jacob G. Bundy; David J. Spurgeon; Claus Svendsen; Peter K. Hankard; Jason M. Weeks; Daniel Osborn; John C. Lindon; Jeremy K. Nicholson (Ecotoxicology, 2004)

Differential regulation of caspase-3 by pharmacological and developmental stimuli as demonstrated using humanised caspase-3 mice - L. E. Kerr; J-L. A. Birse-Archbold; A. Simon; N. Logan; F. Scott; G. Carlson; D. W. Nicholson; J. S. Kelly; J. Sharkey (Apoptosis, 2004)

Inhibition of topoisomerase II overrides the G2/M check points of the cell cycle in EBV-lymphocytes - V. N. Dedov; I. V. Dedova; G. A. Nicholson (Apoptosis, 2003)

Bisucaberin – A dihydroxamate siderophore isolated from Vibrio salmonicida, an important pathogen of farmed Atlantic salmon (Salmo salar) - Günther Winkelmann; Dietmar G. Schmid; Graeme Nicholson; Günther Jung; Duncan J. Colquhoun (BioMetals, 2002)

A study of the impacts of Zn and Cu on two rhizobial species in soils of a long-term field experiment - Amar M. Chaudri; Céline M. G. Allain; Vera L. Barbosa-Jefferson; Fiona A. Nicholson; Brian J. Chambers; Steve P. McGrath (Plant and Soil, 2000)

Detection and Quantification of Individual Fungal Species in Fusarium Disease Complexes of Cereals by Polymerase Chain Reaction (PCR) - P. Nicholson; F. Doohan; H. N. Rezanoor; D. Simpson; P. H. Smith; A. Turner; G. Weston (Cereal Research Communications, 1997)

Caribbean pine in an agroforestry system on the Atherton Tableland in north east Australia - G. B. Applegate; D. I. Nicholson (Agroforestry Systems, 1988)

Enteric inoculation with ERA rabies virus: Evaluation of a candidate wildlife vaccine in laboratory rodents - K. G. Nicholson; Sally P. Bauer (Archives of Virology, 1981)

Interferon response to human diploid cell strain rabies vaccines in man - K. G. Nicholson; E. K. Kuwert; J. Werner; P. Harrison (Archives of Virology, 1979)